Ta’zizu Daur al-Muallim ka ’Unsurin Basyari Muhimmin fi Ta’lim al-Lughah al-‘Arabiyyah li Al-Nathiqina bi Ghairiha - Ismail, Ali Mahmud al-Usmu’i; Qasb, Intishar Muhammad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The future vision of the educational systems concerned with teaching the Arabic language to non-native speakers requires basic skills that must be mastered, such as adaptation, flexibility, accommodating the rapid change in the local and global surrounding environment, the ability to convey ideas by the fastest and most accurate means, and work to develop the capabilities of the teacher and the learner in the educational and learning process, and the absorption of technological means. To develop the competence of the non-Arabic speaking learner and to promote the Arabic language and raise its level among the learners. This research is a descriptive research, and the descriptive research aims to